Produção e composição nutricional de Moringa oleifera cultivada em diferentes espaçamentos e Óleo de soja na dieta de ovinos: produção e qualidade do leite - Longo , Maíza Leopoldina (2020)
In this study, two experiments have been carried out. Experiment 1: The aim was to evaluate the agronomic, productive and nutritional characteristics of Moringa oleifera grown in different spaces between plants and rows. The plants were grown in an area of approximately one hectare, and this was divided into four beds of 211.2 m² each. The treatments were distributed according to the spacing between rows (0.4; 0.8 and 1.2m) and between plants (0.4; 0.6 and 1.0m). The plants were measured for height, the diameter of the crown and the stem every 30 days. For a nutritional assessment, five plants of each treatment have been collected and leaves and stem have been separated in order to determine the levels of dry matter (DM), mineral matter, crude protein (PB), ether extract (EE), neutral detergent fiber (NDF), acid detergent fiber (FDA) and in vitro digestibility of MS, MO, PB and NDF. There was no interaction between the row and plant spacing. Leaf production per ha-1 was greater in the 0.4m spacing between plants (6820.15 kg ha-1); the stem and biomass production was greater in the 0.4m spacing between rows (2261.60 and 7655 , 98kg) ha-1). The nutritional quality of the leaves and stem has not been affected by the planting distance. There has been interaction between plant spacing and rows for the digestibility of dry matter. It is concluded that a greater density of plants can be used in order to have greater use of biomass and greater digestibility of nutrients. Experiment 2: The aim was to evaluate the use of different levels of soybean oil in sheep feed. The milk production, physical and chemical characteristics and the antioxidant power of milk have been evaluated. Eight lactating Pantaneira sheep in a 4x4 double Latin square have been used. The treatments have been distributed according to the amount of oil supplied to the animals 0, 4, 8 and 16g/animal /day of soybean oil. Sheep performance, production, milk quality and lipid oxidation have been evaluated. The consumption, digestibility and quality of milk have not been affected by the consumption of soy oil. There has been an increasing linear effect in the amount of malonaldehyde present in the sheep’s milk. Thus, the use of soybean oil does not interfere in the performance, production and quality of milk. However, the increase in the amount provided boosts the oxidizing effect in sheep’s milk.